Zarządzanie bezpieczeństwem informacji - nowe wyzwanie dla kierownictwa firm w dążeniu do doskonałości - Szomański, Bolesław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Contemporary dependence on computers, Internet and teleinformatic networks has caused that any disruption of integrity, availability or confidentiality of information can bring on serious consequences to the company. Since 2005 ISO 27000 standards on information security management have essentially supplemented and even changed the principles of aspirations for perfection binding in the 1980s. Executives should support all activities connected with preparation and implementation of information security management, provide adequate management structures assuring effective control, technical means and increase staff awareness. They should undertake their activities basing on a risk analysis and prepare their company in case of failure of operation continuity. Executives can pose a serious danger to the security of information through their unaware or deliberate actions. As long as the activities connected with security of information can be delegated, the responsibility for security cannot. Currently, without executives' proper approach to security of information, the aspiration for perfection is out of the question. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 40-47